Effect soil conditioner on some soil characteristics and sugar beet plant growth, nutrients content and yield characters under different water regimes. (Cuestiones de Fisioterapia, 2024)
Water stress is considered as one of the major factors responsible for reducing sugar beet crop productivity. A field experiment was carried out at El-Emam Malek, El-Bostan district, El Behira governorate, Egypt, at 2022-2023, to study the effects of sprayed soil conditioner (glue: 0, 2, 4; 6 %/spraying solution) on some hydrophysical soil characteristics and yield, yield parameters, water use efficiency of sugar beet and some soil properties under different water regimes, WR (100, 85 and 70% from ETo). Results showed the reduction in the irrigation quantities led to increase in sugar beet leaf content from N, P, K and Ca content. So, the highest values were recorded at WR 70%+6% glue in spraying solution (N, 3.50 %), P (1.70%) and 100 WR (K, 3.25% and Ca (1.84%) and water regime treatment 85% scored the highest values for chlorophyll A, B and carotenoids, while the lowest ones were recorded at 70 % WR.